Rotation-Vibration Spectra for Ground State of NaH and Its Isotopes with Explicitly Multireference Configuration Interaction Method (Journal of Atomic and Molecular Sciences, 2016)
High-level ab initio calculations utilizing explicitly correlated multi-referenceconfiguration interaction method (MRCI-F12), considering Davidson modification(Q),core-valence correlation correction(CV) and scalar relativistic correction(SR), were performedto compute the Born-Oppenheimer potential energy curve (PEC) of the groundstate $X^1Σ^+$ of NaH. On the base of the PEC, we obtained vibrational and rotationalenergy levels information of the ground state $X^1Σ^+.$ The vibrational and rotationalspectroscopic constants of $X^1Σ^+$ were compared with the available experimental values.We also report rotation-vibration spectra of the ground state for the isotopes ofNaH, NaD and NaT molecules. The equilibrium internuclear distances $R_e$ and dissociationenergies $D_e$ were calculated to be 1.8865 Å and 15823.29$cm^{-1}$ for the ground state $X^1Σ^+$ of NaH, which are in good agreement with the experimental results of 1.8859 Åand 15815 ± 5$cm^{-1}.$
Keywords: MRCI-F12; NaH; rotational-vibration constants.